НЕМЕЦ ТИЛИ САБАҒЫНДА БАСЛАЎЫШ КЛАСС ОҚЫЎШЫЛАРЫНА ГРАММАТИКАНЫ ҮЙРЕТИЎДЕ ОЙЫНЛАРДЫҢ ӘҲМИЙЕТИ - Есбергенова, Г.Б. (FAN va JAMIYAT, 2025)
This article shows ways to increase the effectiveness of teaching in German language classes using pedagogical technologies, games in the classroom, the types of modern methods used in foreign language teaching methods and their use.